The semantics of questions. Issue 6 (26th July 2019) - Moyer, Morgan C.; Syrett, Kristen
Abstract: Pinning down the semantics of questions poses a challenge for the study of meaning. Unlike most declarative statements, questions cannot be assigned a truth value. They do not assert information about the world that can be easily verified as true or false, or accepted or rejected. Instead, their function as a speech act is to interrogate, to seek information about the world. Thus a truth‐conditional approach to the semantics of questions runs into a dead end. We must therefore evaluate the semantics of questions in terms of the propositions that serve as their answers. But here, a number of questions arise that shape our investigation. What counts as a suitable answer, in general or in a given discourse context? How does the variability of question types within and across the world's languages influence our theory of a unified semantics of questions ? When questions are embedded under a matrix verb like "know, " which takes the question as a sentential complement, how does the semantics of questions feed into the assessment of the proposition expressed by this declarative utterance? What must the subject of the sentence know? Should they be required to know or list an exhaustive list of true answers or one true answer, should they know of the false answers that they are false? What answers are licensed? How can questions reflect a bias on the part of the speaker? These issues lie at the heart of an investigation of the semantics of questions . This article is characterized under: Linguistics > Linguistic Theory Linguistics > Language in Mind and Brain Abstract : Introduction to the semantics of questions.